2021
DOI: 10.1038/s41421-021-00246-5
|View full text |Cite
|
Sign up to set email alerts
|

A cold shock protein promotes high-temperature microbial growth through binding to diverse RNA species

Abstract: Endowing mesophilic microorganisms with high-temperature resistance is highly desirable for industrial microbial fermentation. Here, we report a cold-shock protein (CspL) that is an RNA chaperone protein from a lactate producing thermophile strain (Bacillus coagulans 2–6), which is able to recombinantly confer strong high-temperature resistance to other microorganisms. Transgenic cspL expression massively enhanced high-temperature growth of Escherichia coli (a 2.4-fold biomass increase at 45 °C) and eukaryote … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…For mutants over-expressing candidate genes using shuttle vector pEZ15Asp, recombinant strains of ZM4 (pEZ-0994) and ZM4 (pEZ_cspL) grew significantly better than the control strain ZM4 (pEZ_Ep) (Fig. 6 e–h), which was consistent with previous reports that the overexpression of gene ZMO0994 and heterologous gene cspL can help promote cellular growth significantly at a high temperature [ 26 , 40 ]. In addition, when only groESL operon was overexpressed, the specific growth rate of recombinant strain ZM4 (pEZ_groESL) was significantly higher than that of ZM4 (pEZ_Ep) at high temperatures (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For mutants over-expressing candidate genes using shuttle vector pEZ15Asp, recombinant strains of ZM4 (pEZ-0994) and ZM4 (pEZ_cspL) grew significantly better than the control strain ZM4 (pEZ_Ep) (Fig. 6 e–h), which was consistent with previous reports that the overexpression of gene ZMO0994 and heterologous gene cspL can help promote cellular growth significantly at a high temperature [ 26 , 40 ]. In addition, when only groESL operon was overexpressed, the specific growth rate of recombinant strain ZM4 (pEZ_groESL) was significantly higher than that of ZM4 (pEZ_Ep) at high temperatures (Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, this impact of overexpression of ZMO0994 gene on heat tolerance in Z. mobilis has not been explored yet. In addition to the chaperones discussed above, cold shock protein CspL from the thermophilic bacterium Bacillus coagulans 2–6 was systematically investigated recently, and the results demonstrated that CspL plays a role in heat tolerance, which can promote the growth of diverse microorganisms under heat stress including E. coli DH5α, S. cerevisiae INVSc1, and P. putida KT2440 through binding diverse RNA species at high temperatures [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, due to the enormous interest of LAB, not only as probiotics per se, but also as starter microorganisms in the production of fermented foods, their ability to resist and cope with temperature changes is a feature of the utmost technological importance, given the different temperatures they will undergo during the processing and subsequent refrigeration or frozen storage [ 53 , 54 ]. This temperature tolerance becomes even more significant when talking about probiotics for veterinary use as feed supplements and, within this sector, aquaculture is the most challenging market, due to the extreme temperatures that are reached during the processing of fish feed.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, liver samples collected at 3 days postmortem could meet the requirements of next-generation sequencing (Wang et al, 2020). Because temperature is one of the most important environmental factors affecting the succession of microbes (Zhou et al, 2021), a reasonable explanation for the discrepancy between the previous study and the current study is that the ambient temperature in the present study (5 to 10°C) was substantially lower than that in the previous study (15 to 25°C), resulting in limited growth of microorganisms. This result suggests that in follow-up translational studies, the concept of accumulated degree-days, which integrates postmortem interval and ambient temperature (Heaton et al, 2010), should be used to minimize error caused by temperature fluctuation.…”
Section: Discussionmentioning
confidence: 99%